Learning British Accent Through Short Videos: A Case Study of English Department Student - Tanjung, Renaldy Nova Irawan; Sarmila, Sarmila; Aflahah, Noor Aida; Nadia, Hafizhatu; Nugroho, Suryanto; Mahardika, Dzikrina Aqsha; Purnomo, Eko (Jurnal Keilmuan dan Keislaman, 2023)
This research explores the integration of British accents in the education of bilingual children focusing on the acquisition of foreign languages, particularly emphasizing pronunciation. The study investigates the challenges and strategies related to learning the British accent, while considering the broader context of accent diversity. Through interviews conducted at Muhammadiyah University of Banjarmasin, the responses from students regarding their experiences with British accents were examined. The research reveals that despite the dominance of American accents in the region, there is interest and effort among students to learn British accents. The study also identifies various methods, such as videos and interactions with individuals who use British accents, employed by learners to improve their pronunciation. However, the challenges are substantial, including curriculum limitations, lack of training for educators, and issues related to assessment and infrastructure. While British accents are deemed attractive due to their clear and round pronunciation, the level of difficulty is subjective and influenced by individual interest and intention. In conclusion, mastering pronunciation, specifically British accents, is crucial for effective communication in English, requiring dedicated efforts and appropriate learning resources.